Frequency of peripheral vestibular pathology following traumatic brain injury: a systematic review of literature. (1st July 2021) - Šarkić, Bojana; Douglas, Jacinta M.; Simpson, Andrea; Vasconcelos, Alexandra; Scott, Bethany R.; Melitsis, Lauren M.; Spehar, Stephanie M.
Abstract: Objective: To establish the frequency of occurrence of peripheral vestibular dysfunction in adults who have sustained non-blast-related traumatic brain injury (TBI) as measured through the standard audiological vestibular test battery. Design: A systematic search of English language literature using MEDLINE, EMBASE, PsycINFO, CINAHL, hand-searching of reference lists and SCOPUS author search was conducted from January 1, 1990 to May 14, 2019. Study samples: Twenty-three out of 417 originally identified articles were retained. TBI and peripheral vestibular findings were extracted and synthesised. Results: Quality appraisal using the Oxford Centre for Evidence-Based Medicine (OCEBM) revealed Level 2b as the highest level of evidence. None of the primary studies explored vestibular deficits in acute settings, with data collected from tertiary institutions and in 20 of 23 studies retrospectively. Although retrospective studies provided important data, they fail to control for numerous threats to internal validity. BPPV was the most frequently identified peripheral vestibular deficit following TBI, diagnosed in 39.7% of 239 participants across six of 23 studies. Conclusions: Further prospective longitudinal research into comparative recovery trajectories in patients across TBI severity levels would provide additional information to guide clinical diagnosis, prognosis and management of this patient population.